Some results on quantile-based Shannon doubly truncated entropy. Issue 1 (2nd January 2019) - Kumar, Vikas; Taneja, Gulshan; Chhoker, Samsher
ABSTRACT: Sunoj et al. [(2009). Characterization of life distributions using conditional expectations of doubly (Intervel)truncated random variables. Communications in Statistics – Theory and Methods, 38 (9), 1441–1452] introduced the concept of Shannon doubly truncated entropy in the literature. Quantile functions are equivalent alternatives to distribution functions in modelling and analysis of statistical data. In this paper, we introduce quantile version of Shannon interval entropy for doubly truncated random variable and investigate it for various types of univariate distribution functions. We have characterised certain specific lifetime distributions using the measure proposed. Also we discuss one fascinating practical example based on the quantile data analysis.